Isoetes ×gopalkrishnae (Isoetaceae), a new interspecific sterile hybrid from central India - Singh, Sarvesh Kumar; Shukla, Santosh Kumar; Dubey, Nawal Kishore; Shukla, Pradeep Kumar (Phytotaxa, 2018)
Isoetes ×gopalkrishnae hybr. nov., is described, illustrated and compared with possible parent species. Based on morphological characteristics and habitat conditions, this taxon is considered to represent a sterile hybrid between I. coromandelina and I. panchananii. The new hybrid is amphibious and grows on the exposed shore of an artificial pond. It is known only from a single locality on the Vindhya plateau in Uttar Pradesh, India. It can be distinguished from other taxa by a combination of characters including the lack of a scale, the leaf which is terete in transverse section, velum absent to rudimentary, a sporangial wall with internal pigmentation, rugulate megaspores with a smooth equatorial girdle and microspores with densely echinate to short-cristate ornamentation. It is the first Isoetes hybrid reported from the Indian subcontinent.